Sierra Leone : Poverty Reduction Strategy Paper-Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This report describes the progress made in implementing the Poverty Reduction Strategy Paper for Sierra Leone covering the period 2005-07. Efforts to reform the public sector were not successful. Management and Functional Reviews were conducted for several ministries, departments, and agencies but the recommendations were not implemented. A Senior Executive Service program was also developed but government and development partners could not agree on an implementation strategy and therefore the funds required for implementation were not provided.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet